MR, CT, and Plain Film Imaging of the Developing Skull Base in Fetal Specimens - Nemzek, William R.; Brodie, Hilary A.; Hecht, Stephen T.; Chong, Brian W.; Babcook, Catherine J.; Seibert, J. Anthony (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: The developing fetal skull base has previously been studied via dissection and low-resolution CT. Most of the central skull base develops from endochondral ossification through an intermediary chondrocranium. We traced the development of the normal fetal skull base by using plain radiography, MR imaging, and CT.METHODS: Twenty-nine formalin-fixed fetal specimens ranging from 9 to 24 weeks' gestational age were examined with mammographic plain radiography, CT, and MR imaging. Skull base development and ossification were assessed.RESULTS: The postsphenoid cartilages enclose the pituitary and fuse to form the basisphenoid, from which the sella turcica and the posterior body of the sphenoid bone originate. The presphenoid cartilages will form the anterior body of the sphenoid bone. Portions of the presphenoid cartilage give rise to the mesethmoid cartilage, which forms the central portion of the anterior skull base. Ossification begins in the occipital bone (12 weeks) and progresses anteriorly. The postsphenoid (14 weeks) and then the presphenoid portion (17 weeks) of the sphenoid bone ossify. Ossification is seen laterally (16 weeks) in the orbitosphenoid, which contributes to the lesser wing of the sphenoid, and the alisphenoid (15 weeks), which forms the greater wing.CONCLUSION: MR imaging can show early progressive ossification of the cartilaginous skull base and its relation to intracranial structures. The study of fetal developmental anatomy may lead to a better understanding of abnormalities of the skull base.